The Arabidopsis H3K27me3 demethylase JUMONJI 13 is a temperature and photoperiod dependent flowering repressor - Zheng, Shuzhi (Nat Commun, 2019)
In plants, flowering time is controlled by environmental signals such as day-length and temperature, which regulate the floral pathway integrators, including FLOWERING LOCUS T (FT), by genetic and epigenetic mechanisms. Here, we identify an H3K27me3 demethylase, JUMONJI 13 (JMJ13), which regulates flowering time in Arabidopsis. Structural characterization of the JMJ13 catalytic domain in complex with its substrate peptide reveals that H3K27me3 is specifically recognized through hydrogen bonding and hydrophobic interactions. Under short-day conditions, the jmj13 mutant flowers early and has increased FT expression at high temperatures, but not at low temperatures. In contrast, jmj13 flowers early in long-day conditions regardless of temperature. Long-day condition and higher temperature induce the expression of JMJ13 and increase accumulation of JMJ13. Together, our data suggest that the H3K27me3 demethylase JMJ13 acts as a temperature- and photoperiod-dependent flowering repressor.